GUARANTEES, FIRM SIZE AND FINANCIAL SUSTAINABILITY OF MICRO AND SMALL ENTERPRISES IN KENYA - Paul Ng’ang’a Macharia; Tobias Olweny; Cynthia Stella Waga; Jeff Arodi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
Micro and Small Enterprises play a crucial role in Kenya’s economy, yet their financial sustainability is often weakened by limited credit access and high collateral requirements. This study assesses the effect of guarantees measured through collateral fund requirements on the financial sustainability of Micro and Small Enterprises supported under the National Agricultural and Rural Inclusive Growth Project from 2018 to 2022. Using panel data from 390 enterprises, financial sustainability was evaluated using net profit margin and current ratio, while firm size was measured using the natural logarithm of total assets. Results show that collateral-based guarantees have a significant negative effect on financial sustainability, indicating that stringent collateral demands hinder credit access and strain enterprise performance. The study further finds that firm size positively moderates this relationship, with larger Micro and Small Enterprises better able to absorb the effects of collateral requirements. The study concludes that while guarantees aim to enhance financing, high collateral thresholds can undermine sustainability, particularly for smaller firms. It recommends more flexible guarantee frameworks and policies that strengthen firm capacity to ensure equitable access to finance.